Printable Skin‐Driven Mechanoluminescence Devices via Nanodoped Matrix Modification. Issue 25 (3rd May 2018) - Qian, Xin; Cai, Zheren; Su, Meng; Li, Fengyu; Fang, Wei; Li, Yudong; Zhou, Xue; Li, Qunyang; Feng, Xiqiao; Li, Wenbo; Hu, Xiaotian; Wang, Xiandi; et al.
Abstract: Mechanically driven light generation is an exciting and under‐exploited phenomenon with a variety of possible practical applications. However, the current driving mode of mechanoluminescence (ML) devices needs strong stimuli. Here, a flexible sensitive ML device via nanodopant elasticity modulus modification is introduced. Rigid ZnS:M 2+ (Mn/Cu)@Al2 O3 microparticles are dispersed into soft poly(dimethylsiloxane) (PDMS) film and printed out to form flexible devices. For various flexible and sensitive scenes, SiO2 nanoparticles are adopted to adjust the elasticity modulus of the PDMS matrix. The doped nanoparticles can concentrate stress to ZnS:M 2+ (Mn/Cu)@Al2 O3 microparticles and achieve intense ML under weak stimuli of the moving skin. The printed nano‐/microparticle‐doped matrix film can achieve skin‐driven ML, which can be adopted to present fetching augmented animations expressions. The printable ML film, amenable to large areas, low‐cost manufacturing, and mechanical softness will be versatile on stress visualization, luminescent sensors, and open definitely new functional skin with novel augmented animations expressions, the photonic skin. Abstract : A flexible, sensitive mechanoluminescence (ML) device is demonstrated via matrix elasticity modulus modification. Rigid ZnS:M 2+ (Mn/Cu)@Al2 O3 microparticles are dispersed into soft poly(dimethylsiloxane) (PDMS) film and printed for preparing flexible devices. Via a SiO2 ‐nanoparticle dopant, the ML intensity for small strain is significantly increased. The ML devices achieve intense ML under the weak stimuli of moving skin, which will be significant for photonic‐skin devices.